Data warehouse model for population registration in Kerambitan village Tabanan Regency - Putra, Fathiyarizq Mahendra; Gede Dwidasmara, Ida Bagus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
Kerambitan village is one of the 15 villages in Kerambitan sub-district, Tabanan regency, Kerambitan village has 7 service hamlets. Kerambitan village population has more than 3,338 inhabitants consisting of 1,700 men and 1,638 women with a sex ratio of 103.79. . To realize good governance , it needs to be recorded well so that the information can be utilized by related agencies which can be used for receiving assistance . During this time the process of recording population events such as recording the receipt of assistance is done manually where the information is done in tabular form so it does not clearly describe the respective information groups. Data warehouse (DW or DWH), also known as enterprise data warehouse (EDW), is a system used for reporting and analyzing data, and is considered a core component of business intelligence, The purpose of building a data warehouse is to provide a system that allows the right data to reach the right end user at the right time. Thus, the main purpose of implementing this data warehouse system is to provide relevant and timely information in an easily understood format so that service decisions to the public can be made more efficiently and effectively. the purpose of this research is to form a data warehouse model scheme of population records owned by kerambitan village government and through modeling this data warehouse also provides reliable information from a collection of data , in addition this research also retrieves some information from the data warehouse in build based on kerambitan village population records in this study I chose to use the fact constellation scheme because there are fact tables that are interconnected with dimension tables and also fact tables that are related to other fact tables. The design model of the data warehouse is designed based on 3 excel table files, each of which has 1 table from the Government of Kerambitan Villages. In this case, 3 reports are proposed to be made based on the query results from the data warehouse. Through the application of a data warehouse that was formed, the executive or government can conduct analysis of the reports generated based on various dimensions that exist.